A H-CNTs material for high-selectivity H2O2 synthesis and preparation method thereof
Through the combination of ulotropine and carbon nanotubes, a highly selective H-CNTs material was prepared, which solved the energy consumption and environmental pollution problems of the H2O2 production process in the prior art, and achieved high selectivity and stability of oxygen reduction Response, reduces production costs and improves safety.
Patent Information
- Application Number
- CN202210620235.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-06-02
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-06-02
AI Technical Summary
The existing H2O2 industrial production process has high energy consumption, environmental pollution and safety risks, and lacks low-cost, high-activity, high selectivity and high stability electrocatalysts, making it difficult to achieve precise control of the two-electronic process.
Using the method of combining ulotropine with carbon nanotubes, high-selective H-CNTs materials were prepared through nitrogen doping and steric hindrance effects to improve the catalytic performance of oxygen reduction reaction.
The formation of high selectivity H2O2 is achieved, the activity and stability of oxygen reduction reaction is improved, the problem of easy breakage of lateral adsorption of oxygen is solved, the production cost is reduced, and the safety and environmental protection of the process are improved.
Smart Images

Figure CN115369440B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalysis, and in particular to an H-CNTs material for high-selective H2O2 synthesis and a preparation method thereof. Background Art
[0002] Hydrogen peroxide (H2O2) is a common chemical in industry. It is widely used for oxidation and disinfection. The demand for H2O2 is expected to exceed 6,000 kilotons in 2024. At present, the industrial production of H2O2 relies on the harsh and expensive anthraquinone process, which requires high-pressure hydrogen, precious metal catalysts and complex post-processing steps. Due to the need for a large amount of organic solvents, a large amount of organic waste liquid is generated, which has an immeasurable impact on the environment. In addition, the high concentration of H2O2 produced by this process is potentially dangerous during transportation and storage. The electrocatalytic oxygen reduction reaction of the two-electron process to produce H2O2 has the advantages of low energy consumption, safety and environmental protection, and does not require large equipment, saving transportation and storage costs. It has become a green method that is expected to replace the traditional anthraquinone process. However, the four-electron process of ORR usually competes with the two-electron method required for the generation of H2O2. Therefore, in order to achieve precise control of the electrochemical synthesis of H2O2 by two-electron ORR and the commercialization of the system, high requirements are placed on low-cost, high-activity, high-selectivity and high-stability electrocatalysts.
[0003] Nanocarbon materials are promising ORR catalyst materials due to their low price, good conductivity and mechanical properties. For pure carbon catalysts, their inherent weak interaction with oxygen-containing intermediates leads to low ORR activity. In the ORR process, by adjusting the electronic structure of the catalyst, the binding strength between the intermediate and the catalyst surface can be effectively improved, which has a great influence on the activity of the catalyst. Therefore, the development of carbon-based catalysts with adjustable electronic structures is of great significance for adjusting the binding energy of the intermediates, reaction selectivity and further improving the catalytic performance. Summary of the invention
[0004] In view of the problems existing in the prior art, the purpose of the present invention is to provide an H-CNTs material for high-selective H2O2 synthesis and a preparation method thereof.
[0005] The purpose of the present invention is achieved by the following technical solutions:
[0006] A method for preparing H-CNTs material for high-selectivity H2O2 synthesis comprises the following steps:
[0007] Step 1, weighing hexamethylenetetramine and carbon nanotubes and placing them in a flask, adding ultrapure water and mixing them evenly to obtain a first mixed solution;
[0008] Step 2, placing the first mixed solution in an oil bath, heating, refluxing and stirring to obtain a second mixed solution;
[0009] Step 3, filtering and washing the second mixed liquid, and then vacuum drying to obtain H-CNTs powder.
[0010] Preferably, steps 1 to 3 are all carried out under air conditions without the need to introduce protective gas.
[0011] Preferably, in step 1, the mass ratio of hexamine, carbon nanotubes and ultrapure water is 1-5:0.05:100.
[0012] Preferably, in step 2, the temperature of the oil bath is 80° C. and the stirring time is 4 hours.
[0013] Preferably, in step 3, the filtration is performed by suction filtration using 20 μm filter paper.
[0014] Preferably, in step 3, washing includes first washing with ultrapure water and then washing with ethanol.
[0015] Preferably, in step 3, washing is performed sequentially with anhydrous ethanol for 2 times and deionized water for 2 times, with 200 mL used for each washing.
[0016] Preferably, in step 3, the vacuum drying temperature is 70° C. and the drying time is 12 h.
[0017] An H-CNTs material for high-selective H2O2 synthesis is prepared by using the above preparation method.
[0018] Preferably, the H2O2 selectivity of the H-CNTs can be up to 95%.
[0019] The beneficial effects of the present invention are:
[0020] 1. The high H2O2 selective catalytic material H-CNTs prepared by the present invention improves selectivity through nitrogen doping and steric hindrance effect of hexamethylenetetramine.
[0021] 2. The present invention uses hexamethylenetetramine as a nitrogen source to introduce nitrogen elements into carbon nanotubes to improve the activity of the ORR two-electron process, thereby obtaining a high-performance two-electron ORR catalyst material.
[0022] 3. The present invention utilizes the steric effect of the adamantane structure of hexamethylenetetramine to further improve the selectivity of H2O2 produced by oxygen reduction, solves the problem of easy breakage of lateral oxygen adsorption, and further improves the selectivity of H2O2 produced by oxygen reduction.
[0023] 4. The invention has simple process, ingenious design, safety and controllability, and low cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.
[0025] Figure 1 This is a scanning electron microscope image of H-CNTs of an embodiment of the present invention:
[0026] Figure 2 The transmission electron microscopy images of H-CNTs of the embodiments of the present invention are as follows: (a) is a transmission electron microscopy image of H-CNTs; (b) is a high-resolution transmission electron microscopy image of H-CNTs (inset: corresponding SAED image);
[0027] Figure 3 The physical phases of H-CNTs in the embodiments of the present invention are as follows: (a) X-ray diffraction pattern of H-CNTs; (b) Raman pattern of H-CNTs;
[0028] Figure 4 XPS of H-CNTs of the present invention: (a) high-resolution spectrum peak of C 1s; (b) high-resolution spectrum peak of N 1s;
[0029] Figure 5 The electrochemical performance test diagram of H-CNTs in the embodiment of the present invention; (a) RRDE of the original sample and H-CNTs; (b) the electron transfer number and H2O2 selectivity curve obtained according to RRDE;
[0030] Figure 6 This is a graph showing the H2O2 yield of H-CNTs in an embodiment of the present invention;
[0031] Figure 7 It is the ORR stability diagram of H-CNTs in the embodiment of the present invention;
[0032] Figure 8 Ce at 400nm wavelength in the embodiment of the present invention 4+ Calibration curve of absorbance versus concentration. DETAILED DESCRIPTION
[0033] In order to more clearly illustrate the present invention and have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0034] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.
[0035] The present invention is further described in conjunction with the accompanying drawings and the following embodiments.
[0036] Example 1
[0037] The catalytic material H-CNTs with high H2O2 selectivity provided in this embodiment comprises the following steps:
[0038] Step 1, weigh 2.8 g of hexamethylenetetramine and 50 mg of commercial carbon nanotubes (number / CAS number: XFM62 / 1333-84-6, purchased from Nanjing Xianfeng Nanomaterial Technology Co., Ltd.) into a flask, and add 100 mL of ultrapure water;
[0039] Step 2, adding the solution obtained in step 1 into an oil bath, stirring and refluxing at 80° C. in the oil bath under air for 4 h;
[0040] Step 3, the product obtained in step 2 was filtered with 20 μm filter paper, and washed with anhydrous ethanol twice and deionized water twice, using 200 mL for each wash;
[0041] Step 4, drying the product obtained in step 3 in a vacuum drying oven for 12 hours at a temperature of 70° C. to obtain H-CNTs powder.
[0042] An H-CNTs material for high-selectivity H2O2 synthesis is prepared by the above preparation method. The H2O2 selectivity of the H-CNTs can reach up to 95%.
[0043] Comparative Example 2
[0044] A catalytic material H-CNTs with high H2O2 selectivity comprises the following steps:
[0045] Step 1, weigh 2 g of hexamethylenetetramine and 50 mg of commercial carbon nanotubes into a flask, and add 100 mL of ultrapure water;
[0046] Step 2, adding the solution obtained in step 1 into an oil bath, stirring and refluxing at 80° C. in the oil bath under air for 4 h;
[0047] Step 3, the product obtained in step 2 was filtered with 20 μm filter paper, and washed with anhydrous ethanol twice and deionized water twice, using 200 mL for each wash;
[0048] Step 4, drying the product obtained in step 3 in a vacuum drying oven for 12 hours at a temperature of 70° C. to obtain H-CNTs powder.
[0049] Example 3
[0050] A catalytic material H-CNTs with high H2O2 selectivity comprises the following steps:
[0051] Step 1, weigh 3 g of hexamethylenetetramine and 50 mg of commercial carbon nanotubes into a flask, and add 100 mL of ultrapure water;
[0052] Step 2, adding the solution obtained in step 1 into an oil bath, stirring and refluxing at 80° C. in the oil bath under air for 4 h;
[0053] Step 3, the product obtained in step 2 was filtered with 20 μm filter paper, and washed with anhydrous ethanol twice and deionized water twice, using 200 mL for each wash;
[0054] Step 4, drying the product obtained in step 3 in a vacuum drying oven for 12 hours at a temperature of 70° C. to obtain H-CNTs powder.
[0055] Example 4
[0056] A catalytic material H-CNTs with high H2O2 selectivity comprises the following steps:
[0057] Step 1, weigh 4 g of hexamethylenetetramine and 50 mg of commercial carbon nanotubes into a flask, and add 100 mL of ultrapure water;
[0058] Step 2, adding the solution obtained in step 1 into an oil bath, stirring and refluxing at 80° C. in the oil bath under air for 4 h;
[0059] Step 3, the product obtained in step 2 was filtered with 20 μm filter paper, and washed with anhydrous ethanol twice and deionized water twice, using 200 mL for each wash;
[0060] Step 4, drying the product obtained in step 3 in a vacuum drying oven for 12 hours at a temperature of 70° C. to obtain H-CNTs powder.
[0061] Example 5
[0062] A catalytic material H-CNTs with high H2O2 selectivity comprises the following steps:
[0063] Step 1, weigh 5 g of hexamethylenetetramine and 50 mg of commercial carbon nanotubes into a flask, and add 100 mL of ultrapure water;
[0064] Step 2, adding the solution obtained in step 1 into an oil bath, stirring and refluxing at 80° C. in the oil bath under air for 4 h;
[0065] Step 3, the product obtained in step 2 was filtered with 20 μm filter paper, and washed with anhydrous ethanol twice and deionized water twice, using 200 mL for each wash;
[0066] Step 4, drying the product obtained in step 3 in a vacuum drying oven for 12 hours at a temperature of 70° C. to obtain H-CNTs powder.
[0067] In order to explain the present invention more clearly, the present invention conducted electrochemical tests and tests in H2O2 synthesis on the H-CNTs prepared in the examples as samples.
[0068] Experimental Example 1
[0069] Characterization tests were performed on the H-CNTs prepared in the examples of the present invention, and the results are as follows:
[0070] Figure 1 is the scanning electron microscope image of H-CNTs; Figure 2 Transmission electron microscopy images of H-CNTs: (a) Transmission electron microscopy image of H-CNTs; (b) High-resolution transmission electron microscopy image of H-CNTs (inset: corresponding SAED image); Figure 3 The physical phases of H-CNTs: (a) X-ray diffraction pattern of H-CNTs; (b) Raman pattern of H-CNTs; Figure 4 XPS of H-CNTs: (a) high-resolution peak of C 1s; (b) high-resolution peak of N 1s; Figure 7 It diagram of ORR stability of H-CNTs.
[0071] Experimental Example 2
[0072] Weigh 5 mg of H-CNTs sample, add 300 μL of distilled water and 700 μL of anhydrous ethanol, then add 20 μL of naphthol, mix well, and disperse by ultrasonic for 30 min.
[0073] 10 μL of sample was taken with a pipette, dropped on the glassy carbon electrode of the ring-disk electrode, and dried in an oven.
[0074] In a 0.1M KOH solution, O2 was introduced for 30 min. The inert glassy carbon electrode loaded with the mixture was used as the working electrode, the carbon rod as the counter electrode, and the mercury oxide electrode as the reference electrode. Then the electrochemical test was started. CV, LSV and RRDE were tested in the potential range of 0.2 to -0.8V. (See Figure 5 )
[0075] Experimental Example 3
[0076] Weigh 5 mg of H-CNTs sample, add 300 μL of distilled water and 700 μL of anhydrous ethanol, then add 20 μL of naphthol, mix well, and disperse by ultrasonic for 30 min.
[0077] Cut a 1 cm × 1 cm carbon cloth, take 200 μL of the sample and drop it on the carbon cloth to obtain a carbon cloth loaded with 1 mg of catalyst.
[0078] The carbon cloth was clamped by a platinum electrode as the working electrode, the carbon rod as the counter electrode, and the mercury oxide electrode as the reference electrode. The yield of H2O2 was tested at an external voltage of -0.5V. (See Figure 6 )
[0079] Experimental Example 4
[0080] Weigh 33.6 mg CeS2O8 and dissolve it in 100 mL 0.1 M H2SO4 solution to make a 1 mM CeS2O8 solution. Prepare 0.2 mM, 0.4 mM, 0.6 mM, and 0.8 mM CeS2O8 solutions at the same time. Test the absorbance of CeS2O8 solutions of different concentrations at a wavelength of 400 nm using an ultraviolet spectrometer. 4+ The absorbance calibration curve.
[0081] The pale yellow CeS2O8 solution reacts with H2O2 to produce Ce 3+ It is a colorless and transparent solution. The concentration of H2O2 can be calculated by comparing the calibration curve. (See Figure 8 )
[0082] Experimental Example 5
[0083] Take 1mL of the electrolyte after the reaction and 3mL of 1mM CeS2O8 solution, mix them and let them stand for 2h. After the reaction is complete, test the absorbance at 400nm. By comparing the calibration curve, the concentration of H2O2 can be calculated, and the total amount of H2O2 produced by the reaction can be obtained, and the yield of H2O2 in the experiment can be obtained (see Figure 6 and Figure 8 ).
[0084] The principle of H-CNTs prepared in the above embodiment of the present invention is as follows: hexamethylenetetramine itself can be used as a nitrogen source to introduce nitrogen into carbon nanotubes, and the pyrrolic nitrogen in nitrogen-doped carbon can improve the activity of the ORR two-electron process. At the same time, the adamantane structure of hexamethylenetetramine has a certain steric effect, which can make the combination of oxygen and catalyst tend to be adsorbed at the end, effectively preventing the oxygen-oxygen bond from breaking and thus converting the intermediate OOH* into H2O, further improving the selectivity of oxygen reduction to H2O2.
[0085] The high H2O2 selective catalytic material H-CNTs prepared in the above embodiment of the present invention improves selectivity through nitrogen doping and steric hindrance effect of urotropine. The present invention uses urotropine as a nitrogen source to introduce nitrogen elements into carbon nanotubes to improve the activity of the ORR two-electron process, thereby obtaining a high-performance two-electron ORR catalyst material.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing H-CNTs material for high-selectivity H2O2 synthesis, characterized in that: The following steps are involved: Step 1, weighing hexamethylenetetramine and carbon nanotubes and placing them in a flask, adding ultrapure water and mixing them evenly to obtain a first mixed solution, wherein the mass ratio of hexamethylenetetramine, carbon nanotubes and ultrapure water is 1-5:0.05:100; Step 2, placing the first mixed solution in an oil bath, heating, reflux and stirring, the temperature of the oil bath is 80° C., and the stirring time is 4 hours to obtain a second mixed solution; Step 3, filtering and washing the second mixed liquid, and then vacuum drying to obtain H-CNTs powder; Steps 1 to 3 are all carried out under air conditions without the need for introducing protective gas.
2. The method for preparing H-CNTs material for high-selectivity H2O2 synthesis according to claim 1, characterized in that: In the step 3, the filtration is performed by suction filtration using a 20 μm filter paper.
3. The method for preparing H-CNTs material for high-selectivity H2O2 synthesis according to claim 1, characterized in that: In step 3, washing includes first washing with ultrapure water and then washing with ethanol.
4. The method for preparing H-CNTs material for high-selectivity H2O2 synthesis according to claim 3, characterized in that: In step 3, the washing is performed in sequence with anhydrous ethanol for 2 times and deionized water for 2 times, with 200 mL used for each washing.
5. The method for preparing H-CNTs material for high-selectivity H2O2 synthesis according to claim 1, characterized in that: In step 3, the vacuum drying temperature is 70° C. and the drying time is 12 h.
6. A H-CNTs material for highly selective H2O2 synthesis, characterized in that: It is prepared by the preparation method described in any one of claims 1 to 5.
7. The H-CNTs material for high-selectivity H2O2 synthesis according to claim 6, characterized in that: The H2O2 selectivity of the H-CNTs is as high as 95%.